2018
DOI: 10.1186/s40635-018-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature and mouse scoring systems as surrogate markers of death in cecal ligation and puncture sepsis

Abstract: BackgroundDespite increasing ethical standards for conducting animal research, death is still often used as an endpoint in mouse sepsis studies. Recently, the Murine Sepsis Score (MSS), Mouse Clinical Assessment Score for Sepsis (M-CASS), and Mouse Grimace Scale (MGS) were developed as surrogate endpoint scoring systems for assessing pain and disease severity in mice. The objective of our study was to compare the effectiveness of these scoring systems and monitoring of body temperature for predicting disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 30 publications
1
83
0
2
Order By: Relevance
“…Strong differences among compartments are likely 67 and the blood compartment constitutes only a small representation of the entire immuno-inflammatory status of the host. Our results strongly indicate that accompanying survival studies (or using a reliable death surrogates 68 , 69 ) should be viewed as an important validation step in 2-hit modeling systems. Lack of such a verification may lead to misleading results from which inappropriate conclusions are drawn.…”
Section: Discussionmentioning
confidence: 64%
“…Strong differences among compartments are likely 67 and the blood compartment constitutes only a small representation of the entire immuno-inflammatory status of the host. Our results strongly indicate that accompanying survival studies (or using a reliable death surrogates 68 , 69 ) should be viewed as an important validation step in 2-hit modeling systems. Lack of such a verification may lead to misleading results from which inappropriate conclusions are drawn.…”
Section: Discussionmentioning
confidence: 64%
“…Decreased cardiac output and blood pressure may be associated with hypothermia (Fig. 1c) [11,37], reinforcing the need to measure body temperature in sepsis mice models.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, these neurological effects were re ected in the impairment of the level of consciousness and activity in the Sepsis group ( Figure S1a,c). The neurological symptoms can be identi ed in the rst hours by MSS [11], but using the A-MSS allows the assessment of autonomic insu ciency evaluating the temperature (Fig. 1c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoring indicated that the mice infected with the steA strain probably died of a heightened immune response. We also checked the body temperatures of mice infected with 5 × 10 5 wt, steA, and compl and found lower body temperatures of steAinfected mice, indicating that probably mice were undergoing sepsis (35).…”
Section: Stea Affects the Pathogenesis Of Salmonella Typhimuriummentioning
confidence: 98%